Pengaruh Belanja Daerah terhadap Pertumbuhan Ekonomi, IPM, dan Kemiskinan di Kalimantan Selatan - Ningrum , Eva Wati; Nuryadin , Muhammad Rusmin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2021)
The research aims to determine how local government expenditure on economic growth, HDI, and poverty in South Kalimantan is influenced. This research uses panel data regression analysis, consisting of 13 districts/cities in South Kalimantan during the 2012-2018 periode. The expenditure variable used in this research is the realization of local government expenditure based on function. The result of the study indicates that local government expenditure in education had no significant effect on economic growth, HDI, and poverty. At the same time, the local government expenditure on health has a significant effect on economic growth, HDI, and poverty.